Killing and letting die: an irrelevant distinction to bioethics - Malik, Mohammad Manzoor (IIUM Press, 2011)
James Rachels’s distinction between killing and letting die maintains that there is morally no difference between killing a terminally ill patient and letting him/her die. Therefore, active and passive euthanasia dichotomy is a distinction without a difference. Hence, if passive euthanasia is allowed, active euthanasia should be permitted too. The paper demonstrated that the distinction between killing and letting die is: (1) irrelevant to euthanasia(2) extraneous to the medical profession, and (3) methodologically degressive. Furthermore, the paper demonstrated invalidity of the bare difference argument of Rachels based on the distinction because of four reasons: (1) irrelevance to American Medical Association’s statement; (2) differences between the cases such as intentionality, causality, and agency; (3) straw man fallacy, (4) and weak analogy. Therefore, the paper concluded that relating the distinction between killings and letting die to bioethics and euthanasia is unjustifiable.